UK medical students’ mental health and their intention to drop out: a longitudinal study - Asta Medisauskaite; Antonia Rich; Milou Silkens; Neha Lagisetty (BMJ Open)
Objective The attrition of medical students is an incredibly important problem feeding into healthcare workforce issues. This study seeks to explore the relationships between various mental health issues and dropout.Design This is a longitudinal study where medical students completed an online questionnaire between November 2020 and February 2021 and those who took part were invited (February–May 2021) to complete the questionnaire again 3 months later.Settings Students from nine geographically spread medical schools in the UK took part in this study.Participants 792 (71.16%) participants filled in the baseline questionnaire and 407 (51.39%) of these students completed the follow-up survey (385 participants were lost to follow-up).Outcome measures Dropout intentions.Exposures Various mental ill-health symptoms using validated scales: emotional exhaustion, insomnia, somatisation, hazardous drinking, anxiety/depression, anorexia tendencies, obsessive-compulsive disorder (OCD), paranoia and bipolar.Results A large number of students met the criteria for mental health disorders (eg, 54.1% insomnia, 37.9% anxiety/depression, 19.4% paranoia) and 19.4% (79) said that they considered dropping out from medical school. Those students who were more emotionally exhausted (Badjusted=0.94, p<0.0001) and expressed higher anxiety/depression symptoms (Badjusted=1.12, p<0.0001), insomnia symptoms (Badjusted=0.69, p<0.0001), somatisation symptoms (Badjusted=0.77, p<0.0001), anorexia tendencies (Badjusted=−0.84, p<0.0001), OCD symptoms (Badjusted=0.61, p<0.0001) and paranoia symptoms (Badjusted=0.52, p<0.0001) expressed significantly stronger intentions to leave their medical education. Hazardous drinking and bipolar symptoms did not predict students’ intention to drop out (p>0.05).Conclusions A substantial number of UK medical students experienced mental ill-health symptoms, about one in five medical students considers leaving medical school, and mental ill-health symptoms contributed to students’ intentions to leave their medical education. Medical schools should improve the learning environment for students and encourage them to seek help to reduce the stigma of mental ill-health symptoms (eg, through education, signposting). It may be useful for medical schools to help applicants/medical students understand whether medical school is the right decision for them and provide them with resources should they wish to leave.